A global systematic review and meta-analysis on correlation between biofilm producers and non-biofilm producers with antibiotic resistance in Uropathogenic Escherichiacoli. (March 2022) - Garousi, Mitra; Monazami Tabar, Sina; Mirazi, Hosein; Asgari, Parnia; Sabeghi, Paniz; Salehi, Astireh; Khaledi, Azad; Ghenaat Pisheh Sanani, Mohammad; Mirzahosseini, Hossein Karballaei
Abstract: Escherichia coli accounts for nearly 80% of community-acquired and 50% of hospital-acquired urinary tract infections (UTI). This study aimed to evaluate the correlation between biofilm producers and Non-biofilm producers with antibiotic resistance in Uropathogenic Escherichia coli (UPEC) isolated from patients with UTI globally. The search was conducted between 1st 2000 to 30 th October 2021 in various databases (PubMed, Scopus, Web of sciences, and Google Scholar) with suitable MeSH terms, and text words. Then, after applying the appropriate inclusion and exclusion criteria on the studies for their selection, the data were analyzed by CMA software. Thirty-seven studies met the eligibility criteria to include. The pooled prevalence of ESBL and MDR isolates were reported 37.9%, and 65.8%, respectively. Biofilm formation varied between 13.3% and 99% all over the world. A total of 74.4% of all isolates were biofilm producers, out of which 28.6%, 35.2%, and 38.6% showed strong, moderate, and weak bioﬁlm. The highest and lowest resistance was against Amoxicillin and Meropenem with the prevalence of 80.8%, and 13%, respectively. Fourteen out of 17(82.35%) studies reported a positive correlation between biofilm and antibiotic resistance. Findings showed high numbers of isolates were able to form biofilm, which is one of the factors of antibiotic resistance, and this has been confirmed by the positive significant correlation between biofilm formation and antibiotic resistance that has been reported by studies included. Therefore, due to the importance of biofilm in the etiology of UTI caused by UPEC, it should be prevented; consequently, bacterial resistance can be reduced and controlled. Highlights: A total of 74.4% of all isolates were biofilm producers. About 28.6%, 35.2%, and 38.6% of biofilm producers showed strong, moderate, and weak bioﬁlm. The highest and lowest resistance was against amoxicillin and meropenem with the prevalence of 80.8%, and 13%, respectively. About 82.35% studies reported a positive correlation between biofilm and antibiotic resistance.